The Concepts of Food Security and the Right to Safe Food From the International and European Perspective - Oana ŞARAMET; A. TOMA-BIANOV (Bulletin of the Transilvania University of Braov • Vol. 5 (54) No. 1 - 2012 Series VII: Social Sciences • Law, 2012)
Food security and the right to safe food are two concepts largely exploited in the international and European discourse and also two juridical realities that have become a matter of ever increasing international and regional concern. In analysing both the conceptualization and the normative settlement of food security and the right to safe food in the United Nations Organization and European Union, this paper suggests that improvements and progresses should be achieved in order to enhance a proactive cooperation between national and international institutions in this particular area.
Keywords: food; security; safe; right